Cell Type-specific Intrinsic Perithreshold Oscillations in Hippocampal GABAergic Interneurons. (15th April 2018) - Kang, Young-Jin; Lewis, Hannah Elisabeth Smashey; Young, Mason William; Govindaiah, Gubbi; Greenfield, Lazar John; Garcia-Rill, Edgar; Lee, Sang-Hun
Highlights: Most parvalbumin-positive basket cells (PVBCs) produced intrinsic perithreshold gamma oscillations. A minority of PVBCs generated intrinsic perithreshold theta, but not gamma, oscillations. CB1 -positive interneurons produced intrinsic perithreshold theta oscillations. Neurogliaform cells and ivy cells generated intrinsic perithreshold theta oscillations. Persistent sodium currents contribute to intrinsic perithreshold oscillations of all five interneuron subtypes. Abstract: The hippocampus plays a critical role in learning, memory, and spatial processing through coordinated network activity including theta and gamma oscillations. Recent evidence suggests that hippocampal subregions (e.g., CA1) can generate these oscillations at the network level, at least in part, through GABAergic interneurons. However, it is unclear whether specific GABAergic interneurons generate intrinsic theta and/or gamma oscillations at the single-cell level. Since major types of CA1 interneurons (i.e., parvalbumin-positive basket cells (PVBCs), cannabinoid type 1 receptor-positive basket cells (CB1 BCs), Schaffer collateral-associated cells (SCAs), neurogliaform cells and ivy cells) are thought to play key roles in network theta and gamma oscillations in the hippocampus, we tested the hypothesis that these cells generate intrinsic perithreshold oscillations at the single-cell level. We performed whole-cell patch-clamp recordings from GABAergic interneurons in the CA1 region of the mouse hippocampus in the presence of synaptic blockers to identify intrinsic perithreshold membrane potential oscillations. The majority of PVBCs (83%), but not the other interneuron subtypes, produced intrinsic perithreshold gamma oscillations if the membrane potential remained above −45 mV. In contrast, CB1 BCs, SCAs, neurogliaform cells, ivy cells, and the remaining PVBCs (17%) produced intrinsic theta, but not gamma, oscillations. These oscillations were prevented by blockers of persistent sodium current. These data demonstrate that the major types of hippocampal interneurons produce distinct frequency bands of intrinsic perithreshold membrane oscillations.